Mild regiospecific alcoholysis and aminolysis of epoxides catalyzed by zirconium(IV) oxynitrate - Shinde, Sandip S.; Said, Madhukar S.; Surwase, Trupti B.; Kumar, Pradeep (Tetrahedron Letters, 2015)
A regiospecific method for the ring-opening reaction of epoxides by the primary, secondary, tertiary alcohols, and aryl, aliphatic amines has been developed using non-toxic metal nitrate salt as a catalyst. The best results were obtained using zirconium(IV) oxynitrate among the various screened metal nitrate salts. The reported protocol works efficiently for styrene epoxide and aliphatic as well. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Alcoholysis; Aminolysis; Epoxide; Lewis acid; Zirconia

New butenolide cinnamate and other biological active chemical constituents from Polygonum glabrum - Said, Madhukar S.; Chinchansure, Ashish A.; Nawale, Laxman; Durge, Ankita; Wadhwani, Ashish; Kulkarni, Smita S.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2015)
Phytochemical investigation of the methanol extract of the aerial parts of Polygonum glabrum afforded one new natural product (-)-2-methoxy-2-butenolide-3-cinnamate (1) along with six known compounds, -hydroxyfriedalanol (2), 3-hydroxy-5-methoxystilbene (3), (-) pinocembrin (4), sitosterol-(6-O-palmitoyl)-3-O–d-glucopyranoside (5), (-) pinocembrin-5-methyl ether (6) and sitosterol-3-O–d-glucopyranoside (7). Compound 1 showed promising in vitro anti-HIV-1 activity against primary isolates HIV-1(UG070) (X4, subtype D) and HIV-1(VB59) (R5, subtype C) assayed using TZM-bl cell line with IC50 in the range of 15.68-22.43g/mL. The extract showed TI in the range of 19.19-27.37 with IC50 in the range of 10.90-15.55g/mL. Compounds 1, 3 and 4 exhibited in vitro anti-mycobacterium activity against Mycobacterium tuberculosis H37Ra with IC50 values of 1.43, 3.33 and 1.11g/mL in dormant phase and 2.27, 3.33 and 1.21g/mL in active phase, respectively. Compound 4 was found to be the most active antiproliferative with IC50 values of 1.88-11.00g/mL against THP-1, A549, Panc-1, HeLa and MCF7 cell lines.
Keywords: anti-HIV-1; anti-mycobacterium; antiproliferative; phytochemicals; Polygonaceae; Polygonum glabrum

Stereoselective quenching of cedryl carbocation in epicedrol biosynthesis - Shinde, Sandip S.; Navale, Govinda R.; Said, Madhukar S.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2016)
Epicedrol synthase catalyzes the cyclization of achiral diphosphate substrate, (E,E)-farnesyldiphosphate (FPP) into epicedrol. GC-MS analysis of assay extracts obtained by incubating FPP with epicedrol synthase in 21.6 at % H2(18)O buffer showed the molecular ion of 224 for epicedrol. The labeled oxygen study presented here unambiguously demonstrates that the hydroxyl group of the epicedrol synthase enzymatic product, epicedrol, is derived from a water molecule, not from the phosphate moiety of the FPP. (C) 2016 Elsevier Ltd. All rights reserved.

Molybdenum oxide-mediated facile aliphatic nucleophilic fluorination - Said, Madhukar S.; Khandare, Leena; Shinde, Sandip S. (Tetrahedron Letters, 2017)

Acidic handle assemble heterogeneous carbocatalyst for facile aliphatic nucleophilic fluorination - Said, Madhukar S.; Pandole, Satish; Suryavanshi, Amol; Kumar, Pradeep; Gajbhiye, Jayan M. (ChemistrySelect, 2019)
Acidic handle (-SO3H) assemble carbonaceous catalyst synthesized from glucose acts as a modulator for the nucleophilic fluorination reaction. The heterogeneous catalyst works with various alkyl sulfonate, halide and metal fluoride (MF), to offer a high yield of fluorinated products up to 93%. This carbonaceous catalyst is recyclable for more than five times, with no major loss of activity.
Keywords: fluorination; heterogeneous catalysis

Novel fatty alkene from marine bacteria: a thermo stable biosurfactant and its applications - Ram, Hari; Sahu, Amit Kumar; Said, Madhukar S.; Banpurkar, Arun G.; Gajbhiye, Jayant M.; Dastager, Syed G. (Journal of Hazardous Materials, 2019)
In this study, a novel thermo stable biosurfactants, 1-Pentanonacontene (C95H190) a fatty alkene and 3-Hydroxy16-methylheptadecanoic acid (C18H36O3) were isolated from a marine isolate SGD-AC-13. Biosurfactants were produced using 1% yeast extract in tap water as production medium at 24 h in flask and 12 h in bioreactor. Using 16S rRNA gene sequence (1515 bp) and BCL card (bioMerieux VITEK (R)), strain was identified as Bacillus sp. Crude biosurfactant reduced the surface tension of distilled water to 31.32 +/- 0.93 mN/m with CMC value of 0.3 mg/ml. Cell free supernatant showed excellent emulsification and oil displacement activity with stability up to 160 degrees C, pH 6-12 and 50 g/L NaCl conc. Biosurfactants were characterized using FTIR, TLC, HPLC LC-MS and NMR spectroscopy. Cell free supernatant reduced the contact angle of distilled water droplet from 117 degrees to 52.28 degrees and of 2% pesticide from 78.77 degrees to 73.42 degrees while 750 mu g/ml of crude biosurfactant reduced from 66.06 degrees to 56.33 degrees for 2% pesticide and recovered 35% ULO and 12% HWCO from the contaminated sand. To our best of knowledge, this is the first report of thermo stable fatty alkene as a biosurfactant and is structurally different from previously reported, with having potential application in agriculture, oil recovery and bioremediation.
Keywords: Bioremediation; Biosurfactants; Fatty alkene; Thermo stability; Wettability

Regioselective one-pot synthesis of 3-fluoro-imidazo[1,2-a]pyridines from styrene - Said, Madhukar S.; Mishra, Ankita; Pandole, Satish; Nayak, Rashmi A.; Kumar, Pradeep; Gajbhiye, Jayant M. (Asian Journal of Organic Chemistry, 2019)
A one-pot synthesis of C-3 fluorinated imidazopyridines (F-IMPY) is reported under the additive-free conditions from commercially available styrene and 1-fluoropyridinium tetrafluoroborate as a fluorine source. The substrate styrene undergoes keto-bromination/condensation/fluorination transformation in three sequential steps to furnish F-IMPY. This one-pot synthesis method exhibits broad substrate scope and good functional group tolerance with a good yield (up to 82%).
Keywords: fluorination; imidazopyridines (F-IMPY); One-pot synthesis

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2019)
A sesquiterpene epicedrol cyclase mechanism was elucidated based on the gas chromatography coupled to electron impact mass spectrometry fragmentation data of deuterated (H-2) epicedrol analogues. The chemo-enzymatic method was applied for the specific synthesis of 8-position labelled farnesyl pyrophosphate and epicedrol. EI-MS fragmentation ions compared with non-labelled and isotopic mass shift fragments suggest that the H-2 of C6 migrates to the C7 position during the cyclization mechanism.

Approach to nigericin derivatives and their therapeutic potential - Sahu, Amit Kumar; Said, Madhukar S.; Hingamire, Tejashri; Gaur, Megha; Khan, Abujunaid; Shanmugam, Dhanasekaran; Barvkar, Vitthal T.; Dharne, Mahesh S.; Bharde, Atul A.; Dastager, Syed G. (RSC Advances, 2020)
A new nigericin analogue that has been chemically modified was synthesized through a fluorination process from the parent nigericin, produced from a novel Streptomyces strain DASNCL-29. Fermentation strategies were designed for the optimised production of nigericin molecule and subjected for purification and structural analysis. The fermentation process resulted in the highest yield of nigericin (33% (w/w)). Initially, nigericin produced from the strain DASNCL-29 demonstrated polymorphism in its crystal structure, i.e., monoclinic and orthorhombic crystal lattices when crystallised with methanol and hexane, respectively. Furthermore, nigericin produced has been subjected to chemical modification by fluorination to enhance its efficacy. Two fluorinated analogues revealed that they possess a very potent antibacterial activity against Gram positive and Gram negative bacteria. To date, the nigericin molecule has not been reported for any reaction against Gram-negative bacteria, which are increasingly becoming resistant to antibiotics. For the first time, fluorinated analogues of nigericin have shown promising activity. In vitro cytotoxicity analysis of fluorinated analogues demonstrated tenfold lesser toxicity than the parent nigericin. This is the first type of study where the fluorinated analogues of nigericin showed very encouraging activity against Gram-negative organisms; moreover, they can be used as a candidate for treating many serious infections.

Effect of tert-alcohol functional imidazolium salts on oligomerization and fibrillization of amyloid beta (1-42) peptide - Said, Madhukar S.; Navale, Govinda R.; Yadav, Ashok; Khonde, Nilesh; Shinde, Sandip S.; Jha, Anjali (Biophysical Chemistry, 2020)
Imidazolium based IL's has gained vast interest in developing biological applications. Oligomerization and fibrillization of amyloid beta (1-42) peptide are mainly responsible for the extra-neuronal deposition of amyloid fibrils in neurodegenerative disorders like Alzheimer's disease (AD). Here, we report an effect of tert-BuOH-functional imidazolium ILs on oligomerization and fibrillization of amyloid beta (1-42) Peptide in vitro. In this study, a series of these [alkyl-(t)OHim][OMs] ILs with methyl sulphonate counter anion by varying alkyl chains were used. Among the seven protic ILs, four showed strong binding and inhibition activity for the formation of amyloid beta (1-42) aggregation by using Thioflavin T fluorescence binding assay. The secondary structural analysis of the peptide, pre-incubated with active ILs shows the loss of ordered beta-sheet amyloid structure. The longer alkyl chain ILs showed that an increased in amyloid binding and hence an inhibition effect on amyloid aggregation was enhanced. Thus, we propose that ILs could be presented as potential candidates for therapeutic intervention against Alzheimer's disease (AD).
Keywords: Aggregation; Amyloid beta (1-42) peptide; Biofilm inhibitor; Imidazolium ionic liquid

New TBAF complex, highly stable, facile and selective source for nucleophilic fluorination: applications in batch and flow chemistry - Said, Madhukar S.; Khonde, Nilesh S.; Thorat, Meghana N.; Atapalkar, Ranjit S.; Kulkarni, Amol A.; Gajbhiye, Jayant; Dastager, Syed G. (Asian Journal of Organic Chemistry, 2020)
Natural polysaccharides supported tetrabutylammonium fluoride (TBAF) complexes are prepared and found to be highly stable and selective fluoride source for well-renowned nucleophilic (SN2 type) fluorination reactions for the first time. Bacterial cellulose, plant cellulose, pectin, and starch derived TBAF complexes are synthesized, characterized (using SEM, TEM, and NMR techniques) and studied for their stability and reactivity. Heterogeneous bacterial cellulose-TBAF complex (NBu4(Bac-cell-OH)F) 1 was found to be highly stable and non-hygroscopic among all complexes, which gave high yields of fluorinated products in multi-gram scale in shorter reaction time. The primarily developed batch protocol was extended to solid-solid continuous flow reaction using an in-house built screw reactor, which furnished products in a few seconds of residence time (tR=20-25 sec) and excellent yields.
Keywords: Flow synthesis; fluorination; green chemistry; Sustainable Chemistry

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis (Retraction of Vol 9, Pg 28258, 2019) - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2020)
Retraction of `Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis' by Madhukar S. Said et al., RSC Adv., 2019, 9, 28258-28261.

Total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate and its antimicrobial potentials - Said, Madhukar S.; Udavant, Rohini; Sahu, Amit Kumar; Khan, Abujunaid; Nayak, Rashmi; Dastager, Syed G.; Kumar, Pradeep; Gajbhiye, Jayant (Natural Product Research, 2020)
The first total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate (butenolide cinnamate) was achieved using commercially available starting material. The synthesized compound was found to have promising antibacterial activity against Gram-negative strainsEscherichia coli(ATCC 8739),Salmonella typhimurium(ATCC 23564) andPseudomonas aeruginosa(ATCC 19154) with a minimum inhibitory concentration of 2.0 mu g/mL, 1.0 mu g/mL and 2.0 mu g/mL, respectively. Notably, the compound was more potent against Gram-negative test strains than the Gram-positive test strains.
Keywords: antibacterial activity; butenolide cinnamate; Total synthesis

Metal-free, Tf2NH-catalyzed 1, 6-conjugate addition of imidazopyridine to para-quinone methides: easy access to C3-functionalized triarylmethane imidazopyridine - Khonde, Nilesh S.; Said, Madhukar S.; Sabane, Jagjivan K.; Gajbhiye, Jayant M.; Kumar, Pradeep (Tetrahedron, 2021)
An inexpensive and commercially available Tf2NH-catalyzed 1,6-conjugate addition of imidazopyridine (IMPY) heterocycles to para-quinone methides (p-QMs) is reported. The present transformation provides a diverse class of C3-functionalized triarylmethanes heterocyclic derivatives of imidazopyridine. These metal-free transformations provided a very broad substrate scope of conjugate addition product with a high yield up to 97% within a short duration. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: 1; 6-Conjugate addition; Bronsted acid; C3-functionalization; Imidazopyridine; para-Quinone methide

Antifungal compound from marine Serratia marcescens BKACT and its potential activity against Fusarium sp. - Kharat, Bharat A.; Said, Madhukar S.; Dastager, Syed G. (International Microbiology, 2022)
Ecofriendly biocontrol agents to control pathogenic fungi are in demand globally. The present study evaluated the antifungal potentials of marine bacteria Serratia marcescens BKACT against eight different Fusarium species. A highest 75.5 +/- 0.80% of mycelial inhibition was observed against Fusarium foetens NCIM 1330. Structural characterization of the purified compound was analyzed by GC-MS and NMR techniques; based on the analysis, it is confirmed as 2, 4-di-tert butyl phenol (2, 4-DTBP) with chemical structure C14H22O. At 0.53 mM concentration, purified compound inhibited complete spore germination of F. foetens NCIM 1330. In vitro assay showed complete inhibition of F. foetens NCIM 1330 on the wheat seeds. Tested concentration does not show any toxic effect on germination of the seeds. By this study, we conclude that, 2, 4-DTBP is a suitable candidate to be used as biocontrol agent against Fusarium infection.
Keywords: 2; 4; di-tert butyl phenol; Fusarium sp; marine; Serratia marcescens

Enceleamycins A-C, furo-naphthoquinones from amycolatopsis sp. MCC0218: isolation, structure elucidation, and antimicrobial activity - Khan, Abujunaid; Said, Madhukar S.; Borade, Balasaheb R.; Gonnade, Rajesh; Barvkar, Vitthal; Kontham, Ravindar; Dastager, Syed G. (Journal of Natural Products, 2022)
Three novel furo-naphthoquinones, enceleamycins A-C (1-3), and a new N-hydroxypyrazinone acid (4) were identified from the strain Amycolatopsis sp. MCC 0218, isolated from a soil sample collected from the Western Ghats of India. Their chemical structure and absolute and relative configurations were established by 1D and 2D NMR spectroscopy, single-crystal X-ray crystallography, and high-resolution mass spectrometry. Compounds 1 and 3 were active against methicillin-susceptible and -resistant Staphylococcus aureus with MIC values of 2-16 mu g/mL.

Isolation and structural characterization of exopolysaccharide from marine Bacillus sp. and its optimization by Microbioreactor - Wagh, Vasudev S.; Said, Madhukar S.; Bennale, Jagadish S.; Dastager, Syed G. (Carbohydrate Polymers, 2022)
In the present study, a cost-effective, robust Microbioreactor based production optimization of levan like exopolysaccharide from marine Bacillus sp. SGD-03 was analysed. FE-SEM analysis has showed the significant fibrillar structure of EPS. Size exclusion chromatography and other analytical data revealed that, produced EPS has a molecular weight of 1.0 x 10(4) Da and is composed of fructose monosaccharide with hydroxyl, carbonyl, and ether groups. The backbone structure of EPS has a branching pattern of beta-(2,6) linkages which confirms the similarity with available levan like polymers. The cost-effective media composition for levan production was demonstrated. The maximum yield of crude levan obtained was 123.9 g/L by response surface methodology using robust BioLector Pro Microbioreactor, and same has been validated with shake flask, 1 L and 10 L pilot-scale fermentation.
Keywords: EPS; marine; Microbioreactor; Optimization; structure

Antiviral and ROS scavenging potential of Carica papaya Linn and Psidium guajava leaves extract against HIV-1 infection - Jadaun, Pratiksha; Shah, Prachibahen; Harshithkumar, R.; Said, Madhukar S.; Bhoite, Shubhangi P.; Bokuri, Sowmya; Ravindran, Selvan; Mishra, Neetu; Mukherjee, Anupam (BMC Complementary Medicine and Therapies, 2023)
Antiretroviral therapy is the only treatment option for HIV-infected patients; however, it has certain drawbacks in terms of developing multiple toxic side effects. Thus, there is a continuous need to explore safe and efficacious anti-retroviral agents. Carica papaya Linn and Psidium guajava are known for their various biological activities. In this study, we characterized the bioactive fractions of methanolic leaves extract from both plants using the High-resolution electrospray ionization mass spectrometry (HR-ESI-MS) technique, followed by the investigation of their potential as anti-HIV-1 and antioxidant agents through in vitro mechanistic assays. The anti-HIV-1 activity was examined in TZM-bl cells through luciferase gene assay against two different clades of HIV-1 strains, whereas the intracellular ROS generation was analyzed by Fluorescence-Activated Cell Sorting. Additionally, the mechanisms of action of these phyto-extracts were determined through the Time-of-addition assay. The characterization of Carica papaya Linn and Psidium guajava leaves extract through HR-ESI-MS fragmentation showed high enrichment of various alkaloids, glycosides, lipids, phenolic compounds, terpenes, and fatty acids like bioactive constituents. Both the phyto-extracts were found to be less toxic and exhibited potent antiviral activity against HIV-1 strains. Furthermore, the phyto-extracts also showed a decreased intracellular ROS in HIV-1 infected cells due to their high antioxidant potential. Overall, our study suggests the anti-HIV-1 potential of Carica papaya Linn and Psidium guajava leaves extract due to the synergistic action of multiple bioactive constituents.
Keywords: anti-HIV-1 activity; Anti-retroviral; Bioactive constituents; Carica papaya Linn; Cytotoxicity; HR-ESI-MS; Psidium guajava; reactive oxygen species

Organocatalytic route to the enantioselective synthesis of syn/ anti-α-hydrazino-γ-fluoro alcohols - Khonde, Nilesh S.; Said, Madhukar S.; Danve, Shivam S.; Kumar, Pradeep (Tetrahedron Letters, 2024)
A general organocatalytic method has been developed for the asymmetric synthesis of alpha-hydrazino-gamma-fluoro alcohols, a precursor to syn/anti-1,3-fluoro amines. The strategy employs alpha-fluorination catalyzed by prolinederived catalyst, (S)-alpha,alpha-bis[3,5-bis(trifluoromethyl)phenyl]-2-pyrrolidinemetha nol trimethylsilyl ether followed by Horner-Wadsworth-Emmons (HWE) olefination of aldehydes, and proline-catalyzed alpha-amination as the key steps. The title compounds showed excellent diastereoselectivity (up to 99:1) and enantioselectivity (up to 99 %).
Keywords: alpha-Amination; alpha-Fluorination; diastereoselectivity; Enantioselectivity; HWE olefination; organocatalyst

Marine Arthrobacter enclensis NIO-1008T as a salicylic acid producing biocontrol agent against Fusarium oxysporum - Kharat, Bharat A.; Said, Madhukar S.; Dastager, Syed G. (European Journal of Plant Pathology, 2026)
The importance of microorganisms in plant growth promotion (PGP) and disease control has long been acknowledged. However, marine bacteria have been largely neglected in agricultural applications. In this study, previously identified marine strain Arthrobacter enclensis NIO-1008T has been explored for mitigation of Fusarium oxysporum NCIM 1281 infestation on wheat plants. A genome analysis study confirmed strain NIO-1008T has protein encoding genes associated with stress tolerance, antifungal activity and PGP. A growth attributes study showed strain NIO-1008T has the ability to grow at 4-11 pH, 6% NaCl and in presence of heavy metals. PGP traits, such as ammonia, siderophore and total indole (640 +/- 9 mu g/mL), were also confirmed. Moreover, an antagonistic assay showed 66 +/- 2% F. oxysporum mycelial growth inhibition. Furthermore, NMR data confirmed strain NIO-1008T produced salicylic acid (SA), which inhibited spore germination and mycelial growth. A greenhouse pot experiment showed that disease incidence significantly reduced to 70% in the presence of strain NIO-1008T, and 45.7% in SA, compared to control wheat plants. This study concludes A. enclensis NIO-1008T is a potential biocontrol candidate against F. oxysporum.
Keywords: F. oxysporum; Antifungal compound; Biocontrol activity; Marine bacteria; Salicylic acid